Pemanfaatan Limbah Bulu Ayam sebagai Arang Aktif dalam Menurunkan Kadar Amonia (NH3) dan Total Suspended Solid (TSS) Limbah Cair Rumah Pemotongan Ayam - Putri, Risna Ade; Santjoko, Herman; Suyanto, Adib; Suwerda, Bambang (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2024)
Poultry slaughterhouses are generate significant waste, including both solid and liquid waste.The solid waste produced such as chicken feathers, if not utilized will poluute the environment. Similarly, the liquid waste contains high levels of organic matter. Two important parameters of this waste are ammonia and TSS levels that can be harmful to humans and can be dangerous to aquatic life. One method of wastewater treatment is using activated charcoal. In this study, activated charcoal made fom chicken feather waste was used a way to utilize the solid waste produced by poultry slaughterhouses. This study is a quasi-experimental re-search using a Time Series Design. The study employed activated charcoal with variations in mass of 0,5 grams, 1 grams and 1,5 grams, packaged in dip bags and exposed to the wastewater for 10 minutes. The wastewater was added in 150 ml intervals for a total six addition.The results showed that chicken feather activater charcoal can reduce ammonia and TSS levels, with the most effective variations respectively are 0,5 grams and 1.5 grams. Additionally, chicken feather activated charcoal at 0,5 grams, 1 grams and 1,5 grams also increased the pH value of the poultry slaughterhouse wastewater.